Graph analysis of semantic word association among children, adults, and the elderly - Zortea,Maxciel (2014)
This study used graph analysis to investigate how age differences modify the structure of semantic word association networks of children and adults and if the networks present a small-world structure and a scale-free distribution which are typical of natural languages. Three age groups of Brazilian Portuguese speakers (children, adults and elderly people) participated in the experiment. Quantitative and qualitative measures suggested that adults and elderly speakers have similar network structures. Children's network showed fewer nodes, connections and clusters, and longer inter-node distances. All networks presented a small-world structure, but they did not show entirely scale-free distributions. These results suggest that from childhood to adulthood, there is an increase not only in the number of words semantically linked to a target but also an increase in the connectivity of the network.